Job helping & restraining factors: Effect on employee motivation - MONICA, DR. BENITA. S.; MS. M. NISHANTHI (The journal of contemporary issues in business and government, 2020)
The motivation of employees should be seen as a force that influences the leaders to attain specific goals and objectives of the organisation. Fundamental reason for this study is to find out what sort of elements impact employee Motivation. The samples are collected from 75 employees working in the retail industry (household appliances) through a self-managed survey. Regression analysis is used to identify the influence of employee motivation on employee performance, using four variables: employee inspiration, employee execution, helping variables, and adequacy. The consequences of this review indicate that there is a necessary and encouraging relation between the motivation of employees and the performance of employees. In addition, it is reasoned that intrinsic rewards have a large amount of huge positive relationships with representative execution and worker inspiration.